Germline-targeted baboon apolipoprotein L-1 protects mice against African trypanosomes - Sara Fresard; Sarah J. Pangburn; Kayla Leiss; Daphne Boodwa-Ko; Daniella Kovacsics; Chris J. Schoenherr; Jeremy S. Rabinowitz; Aris N. Economides; Li Li; Weigang Qiu; Bernardo Gonzalez-Baradat; Alessandro Rosa; et al. (Proceedings of the National Academy of Sciences, 2026)
Some primates are immune to infection by most African trypanosome parasites due to apolipoprotein L-1 (APOL1), a primate-specific ion channel-forming protein. Our long-term objective has been to reduce African trypanosomiasis in livestock by genetic bioengineering of cattle with primate APOL1 . To select which primate APOL1 , we analyzed Papio ssp. APOL1 proteins and found that Papio hamadryas APOL1 was a strong candidate for transgenic animal production based on its trypanosome-killing capacity, ion channel properties, and stability. We generated seven transgenic murine lines based on the P. hamadryas APOL1 sequence and used these mice to investigate the level of APOL1 expression required for trypanosome immunity in vivo. We challenged the murine lines with three human and four livestock trypanosome isolates. P. hamadryas APOL1 provided protection against all of the human and three of the livestock trypanosome isolates, though not against Trypanosoma vivax despite the logical hypothesis that APOL1 plays a role in primate immunity to that parasite. Occasionally, lower APOL1 expression in heterozygote mice selected for the emergence of APOL1 resistant parasites in several trypanosome spp. Alarmingly, these resistant parasites were also resistant to high levels of APOL1 in homozygous mice, indicating an increase in virulence. A more-highly expressed chimeric APOL1 transgene encoding Homo sapiens APOL1 with the P. hamadryas APOL1 C-terminus was more effectively protective in heterozygote mice; however, we could not produce homozygous mice, suggesting endogenous toxicity to the mice. Together, these data bear relevance to our long-term objective to generate transgenic APOL1 cattle, the feasibility of which is discussed.